The phenomenology of psychological maladjustment of the internship doctors at modern conditions of professional activity - V. V. Vyun (Journal of Education, Health and Sport, 2017)
Doctors’ individual, personal, social and psychological factors, as well as mechanisms of psychological adaptation to professional activity have been distinguished. Both objective and subjective criteria of efficiency of internship doctors (ID) adaptation to professional activity are discussed. Specificity and clinical manifestations of psychological disorders in ID was described. High level of disadaptation is revealed at 9.2% of men and 12.5% of women; the expressed disadaptation level had 10.3% of men and 14.0% of women; moderate level of disadaptation had 36.2% and 42.1% of the persons under observation, respectively. The specificity of clinical and psychologic adapational disorders in ID have been determined. The following types of maladaptive reactions were detected: asthenic (25.5%), hyperesthesia(21.6%), depressive (16.2%), psychosomatic (14.2%), listless (11.4%), addictive (11.1%). Based on the data obtained reflecting the mechanisms of adaptational disorders to the professional medical activity, we have developed methods of correction and prevention of these disorders with the use of complex psychotherapeutic and psychoeducational methods.